Echocardiographic assessment of left ventricular hypertrophy in patients of chronic kidney disease - Behera, Bijaya K.; M., Sanjay (International Journal of Research in Medical Sciences, 2017)
Background: Present study was conducted with an objective to study the prevalence of left ventricular hyper trophy (LVH) by echocardiography in patients with chronic kidney disease (CKD) and to find out correlation of left ventricular hypertrophy with severity of chronic kidney disease. Methods: From November 2012 to September 2014, 100 chronic kidney disease patients who were admitted in hospital or attended on OPD basis for dialysis were taken for study. Detailed history, clinical evaluation, laboratory investigations and echocardiography was carried out. The diagnosis of CKD was made on basis of serum creatinine more than 1.5 mg/dl which remained constantly for more than 3 months. Patients with mild, moderate and severe CKD were having serum creatinine level 1.5-3mg/dl, 3-6mg/dl and > 6mg/dl respectively. Glomerular filtration rate (GFR) was calculated by modification of diet in renal disease (MDRD) equation. Cut-off for CKD was taken to be <60ml/min / 1.73m2 as per existing guidelines. Results: Out of 100 patients studied, 67 were males and 33 were females. All patients were selected randomly. Majority of the patients were in the age group of 61 -70 years (41%). In the present study, it was found that left ventricular mass index (LVMI) which reflects LVH showed a progressive rise in severity of renal failure with 17 % of mild category of CKD having LVH as compared to 26% of moderate category and 57% of severe category of CKD. Conclusions: Patients with CKD have LVH, which is more marked in patients with severe CKD. So, these patients should have a thorough cardiovascular evaluation even if there were no symptoms, and efforts should be made to prevent LVH, during the early course of renal insufficiency, such as strict control of hypertension, anaemia.